PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI KELAS X DI SMA NEGERI 11 DENPASAR TAHUN PELAJARAN 2023/2024 - Ni Nyoman Mariani; Ni Wayan Sri Prabawati Kusuma Dewi; Putra Baskara, Anak Agung Alit (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Learning is a harmonious combination of educators' teaching activities and learning forstudents, where learning involves interaction between students and educators. To achieve thetargeted competencies, educators must develop learning processes and models in the teaching andlearning process. The problem that will be discussed in this research is whether there is an influenceof the Problem Based Learning (PBL) model on student learning outcomes in the Hindu ReligiousEducation and Character Education subjects for Class This research aims to identify whether or notthere is a significant influence of the Problem Based Learning (PBL) model on student learningoutcomes in the Class X Hindu Religious and Character Education subjects at SMA Negeri 11Denpasar for the 2023/2024 academic year. The method used in research to collect data is data testswhich are carried out and analyzed using the Independent T-Test. The research results show that 1)The results of the Independent T-Test analysis of student learning outcomes obtained a figure of 8.763with a significance level of 0.000. If the significance number Sig. (2-tailed) < 0.05, then thecalculation results prove that the hypothesis H0 is rejected and Ha is accepted. So it can be concludedthat there is a significant influence of the Problem Based Learning (PBL) model on student learningoutcomes in the subjects of Hindu Religious Education and Character Education for Class X at SMANegeri 11 Denpasar for the 2023/2024 academic year.